APLIKASI PENGHITUNG JUMLAH PAKAN SAPI POTONG BERBASIS ANDROID - Wire Bagye; Najamudin Najamudin (Jurnal Informatika dan Rekayasa Elektronik, 2018)
There are million cows West Nusa Tenggara (NTB). considering that it has considerable ruminant potential in this area in West Lombok and Central Lomok. Many beef cattle farms are carried out in West Lombok regency, Central Lombok, many cattle are used by concurrent breeding and combining where beef cattle are fattened from the breeding of farmers. At present forage feed management in several special beef cattle breeders in West Lombok District Suranadi Village, Selebung Village and Central Lombok Pengembur Prabu Village. The results of receiving data obtained from the results of 70% of farmers in feeding are only using estimates that produce the amount of forage and concentrate feed that is not in accordance with the needs of beef cattle. In this study an application for calculating the amount of feed for an Android-based animal was built. The feature in this application uses body length and circumference of data as input then produces the weight of beef cattle, the weight of forage feed, and the weight of the weight of the needs of beef cattle. The application calculation formula refers to beef cattle breeding, which is forage of 10% body weight and 1% weight and cow weight Analysis of problems and needs using the SWOT method, system design using UML (Unified Modeling Language), Extreme Programming as a method of application development. The results of this study indicate that the Android-based feed counter application can help farmers in West Lombok District and Central Lombok Regency in measuring the amount of feed and knowing animal weight. In addition, this application is offline so it is very easy to be used by farmers.